Corrugated steel sheet

The waveform steel plate with a plating material and synthetic resin paint addresses transportation and durability issues by reducing paint thickness and enhancing impact and wear resistance, ensuring stability across temperature extremes.

JP2025017267APending Publication Date: 2025-02-05NIPPON STEEL METAL PROD CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023120313
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-02-05

AI Technical Summary

Technical Problem

Waveform steel plates coated with thick asphalt paint face challenges in transportation due to their bulkiness, and the paint is prone to cracking in extreme temperatures, while also lacking impact and wear resistance.

Method used

A waveform steel plate with a plating material and a synthetic resin paint, such as epoxy or polyester resin, applied to reduce paint film thickness and enhance impact and wear resistance.

Benefits of technology

The solution provides a waveform steel plate with reduced paint film thickness and improved impact and wear resistance, maintaining integrity across various environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025017267000001_ABST
    Figure 2025017267000001_ABST
Patent Text Reader

Abstract

To provide a corrugated steel sheet capable of reducing the thickness of a coating and having shock resistance and wear resistance.SOLUTION: A corrugated steel sheet 1 includes a corrugated steel sheet main body part 2, a plating material 3 provided in the steel sheet main body part 2 and a synthetic resin coating material 4 applied to the plating material 3. The thickness of the synthetic resin coating material 4 is preferably 10 μm or more and 500 μm or less; and the synthetic resin coating material 4 is preferably constituted of at least any of an epoxy resin based coating material and a polyester resin based coating material.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a corrugated steel sheet. [Background technology]

[0002] Corrugated steel sheets are sometimes coated with asphalt to improve corrosion resistance, and the asphalt coating needs to have a thickness of about 1 mm. Patent Document 1 discloses an asphalt-coated corrugated steel sheet for water channels, in which the inner surface of a curved corrugated steel sheet for water channels is coated with an asphalt mixture so that a smooth inner surface is formed.

[0003] Corrugated steel sheets are transported in a stack of multiple sheets, but when a thick asphalt coating is applied, such as in the asphalt-coated corrugated steel sheet disclosed in Patent Document 1, it is difficult to transport the corrugated steel sheets stacked on top of each other, resulting in poor transport efficiency. In addition, asphalt coating is prone to melting at high temperatures in the summer and cracking at low temperatures in the winter. For this reason, a corrugated steel sheet that can be coated with a thin coating is required. In addition, since the corrugated steel sheet may be collided with by soil, driftwood, etc., it is required to have a certain level of resistance to impact and abrasion. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2009-275353 Summary of the Invention [Problem to be solved by the invention]

[0005] Therefore, the present invention has been devised in consideration of the above-mentioned circumstances, and an object of the present invention is to provide a corrugated steel sheet which can be coated with a thin coating film and has impact resistance and abrasion resistance. [Means for solving the problem]

[0006] The corrugated steel sheet according to the present invention is characterized in that it comprises a corrugated steel sheet main body, a plating material provided on the steel sheet main body, and a synthetic resin paint applied to the plating material. Effect of the Invention

[0007] According to the present invention, it is possible to provide a corrugated steel sheet that can be coated with a thin coating thickness and has a desired impact resistance and abrasion resistance. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a perspective view showing an example of a water channel constructed by combining corrugated steel plates according to an embodiment. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of a corrugated steel sheet according to an embodiment. [Diagram 3] FIG. 3 shows the test specimens after the abrasion resistance test in a 0° C. environment, with FIG. 3( a ) showing Comparative Example 1, FIG. 3( b ) showing Invention Example 1, and FIG. [Figure 4] FIG. 4 shows the test specimens after the abrasion resistance test in a 60° C. environment, with FIG. 4( a ) showing Comparative Example 1, FIG. 4( b ) showing Invention Example 1, and FIG. [Diagram 5] FIG. 4 shows the test specimen after the impact resistance test in a 0° C. environment, FIG. 5( a ) shows Comparative Example 1, FIG. 5( b ) shows Invention Example 1, and FIG. [Figure 6] FIG. 6 shows the test specimens after the impact resistance test in a 0° C. environment, with FIG. 6( a ) showing Comparative Example 1 and FIG. 6( b ) showing Invention Example 3. [Figure 7] FIG. 7 shows the test specimens after the impact resistance test in a room temperature environment, with FIG. 7(a) showing Comparative Example 1 and FIG. [Figure 8] FIG. 8 shows test specimens after the salt spray test in a semi-painted state, with FIG. 8(a) showing Comparative Example 1 and FIG. 8(b) showing Invention Example 3. [Figure 9] FIG. 9 shows test specimens after the combined cyclic corrosion test in the half-painted state, with FIG. 9(a) showing Comparative Example 1 and FIG. [Figure 10] FIG. 10 shows test pieces after the submersion test in a semi-coated state, with FIG. 10(a) showing Comparative Example 1 and FIG. [Figure 11] FIG. 11 shows test specimens after a chemical resistance test in which the specimens were immersed in kerosene, with FIG. 11(a) showing Comparative Example 1 and FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, a detailed description will be given of an embodiment of a corrugated steel sheet to which the present invention is applied with reference to the drawings. The configurations in each drawing are shown diagrammatically for the purpose of explanation, and the size of each component, the size comparison between components, etc. may differ from those in the drawings.

[0010] As shown in FIG. 1, the corrugated steel plate 1 is used in waterside areas such as waterways, water tanks, revetments, quays, breakwaters, training dikes, and collecting wells. The corrugated steel plate 1 may be used in vertical shafts, etc. The corrugated steel plate 1 is, for example, a U-shaped flume with a U-shaped cross section, and a waterway 100 is constructed by combining a plurality of the corrugated steel plates. The corrugated steel plate 1 may be formed to have an arc-shaped cross section or a circular cross section. The corrugated steel plate 1 may be a corrugated product, and a corrugated pipe, a corrugated cell, a corrugated water tank, etc. may be constructed by combining a plurality of the corrugated steel plates. The corrugated steel plate 1 may be a liner plate. The corrugated steel plate 1 may be a steel sheet pile.

[0011] As shown in Fig. 2, the corrugated steel sheet 1 includes a steel sheet body 2, a plating material 3, and a synthetic resin coating material 4. The steel sheet body 2 is a corrugated steel sheet. The plating material 3 is a well-known plating material provided on the steel sheet body 2 by plating. For example, a plating material specified by JIS H 8641: zinc hot-dip plating is used as the plating material 3. The film thickness of the plating material 3 is, for example, about 63 µm.

[0012] The synthetic resin paint 4 is applied to the plating material 3. The synthetic resin paint 4 is made of at least one of an epoxy resin paint and a polyester resin paint. The polyester resin paint may be, for example, a polyester urethane resin paint.

[0013] The film thickness of the synthetic resin paint 4 is preferably 10 μm or more and 500 μm or less. If the film thickness of the synthetic resin paint 4 is less than 10 μm, the synthetic resin paint 4 is likely to peel off. If the film thickness of the synthetic resin paint 4 exceeds 500 μm, the film thickness becomes too thick and the synthetic resin paint 4 is likely to crack. For this reason, the film thickness of the synthetic resin paint 4 is preferably 10 μm or more and 500 μm or less.

[0014] In this embodiment, a synthetic resin paint 4 is provided to be applied to the plating material 3. This allows the coating thickness to be thin, and provides a predetermined impact resistance and abrasion resistance. EXAMPLES

[0015] Test specimens for comparative examples and invention examples were prepared, and the performance of the coating was evaluated. In comparative example 1, a plating material was provided on a steel plate, and blown asphalt was applied thereon. In invention examples 1 and 2, a plating material was provided on a steel plate, and a polyester urethane resin-based coating was applied thereon as a polyester resin-based coating. In invention example 3, a plating material was provided on a steel plate, and an epoxy resin-based coating was applied thereon. The blown asphalt applied in comparative example 1 was blown asphalt specified in JIS K 2207 (petroleum asphalt). The plating material applied in comparative example 1 and invention examples 1 to 3 was a plating material specified in JIS H 8641. Table 1 shows an overview of the coating materials in comparative example 1 and invention examples 1 to 3.

[0016] [Table 1]

[0017] First, the abrasion resistance and impact resistance were evaluated for Invention Examples 1 and 2 and Comparative Example 1. In addition, the adhesion, scratch hardness, and rubbing were also evaluated for Invention Examples 1 and 2 and Comparative Example 1.

[0018] Abrasion resistance was evaluated based on the results of the abrasion resistance test according to JIS K 5600-5-9: Abrasion Resistance (Abrasion Wheel Method) and the results of visual inspection of the test specimen after the test. The abrasion resistance test was performed in three different environments: 0°C, normal temperature, and 60°C. Here, the amount of abrasion was evaluated by measuring the amount of abrasion loss in the abrasion resistance test and comparing the amount of abrasion loss with the initial coating amount (= initial coating thickness of paint × area of ​​abrasion zone (2992.3 × 10 (-6) Based on the above, the coating film was evaluated as passing if 50% or more of the initial coating film amount remained based on the coefficient of friction coefficient x specific gravity of coating. The specific gravity of blown asphalt was 1.0 to 1.1 (15°C). The specific gravity of the polyester urethane resin-based coating used in invention examples 1 and 2 was 1.6. The specific gravity of the epoxy resin-based coating used in invention example 3 was 1.5. Among the results of the abrasion amount in the three environments, if it passed at least one of 0°C and 60°C and room temperature, and among the results of the visual observation in the three environments, if it passed at least one of 0°C and 60°C and room temperature, it was evaluated as having abrasion resistance (the "Overall Evaluation" column in Table 3).

[0019] Impact resistance was evaluated based on the amount of wear after the impact resistance test according to JIS K 5600-5-3: Drop weight resistance, and the results of visual observation of the test specimen. The impact resistance test was performed in three environments: 0°C, room temperature, and 60°C. If the test specimen passed at least one of the three environments, 0°C and 60°C, and room temperature, it was evaluated as having impact resistance (see the "Overall evaluation" column in Table 3).

[0020] Adhesion was measured according to JIS K 5600-5-6: Adhesion (cross-cut method), and a grade of 1 or lower was deemed a pass. Scratch hardness was measured according to JIS K 5600-5-4: Scratch hardness (pencil method), and a grade of F or higher was deemed a pass. Rubbing was performed by soaking absorbent cotton in xylene solvent and pressing it hard against the coating surface, rubbing it 40 times at a constant speed, and then performing a rubbing test using the xylol rubbing method in which the coating surface of the rubbed area was visually inspected, and a pass was given to a coating surface that showed no peeling. In the "Details" column in Table 3, the results of adhesion, scratch hardness, and rubbing are shown from left to right.

[0021] Table 2 shows the test overview, and Table 3 shows the results. In Table 3, the test results and the overall evaluation based on the test results are indicated as "O" if they pass, and "X" if they fail.

[0022] [Table 2]

[0023] [Table 3]

[0024] As shown in Tables 2 and 3, the coating thicknesses of Examples 1 and 2 were 30 μm and 70 μm, respectively, and the coating thickness of Comparative Example 1 was 1000 μm. Examples 1 and 2 were evaluated as having abrasion resistance and impact resistance. In contrast, Comparative Example 1 was evaluated as not having abrasion resistance and impact resistance. Thus, Examples 1 and 2 can have a thinner coating thickness than Comparative Example 1, and have impact resistance and abrasion resistance.

[0025] In detail, in the results of the wear amount in the abrasion resistance test, in Comparative Example 1, the applied asphalt coating peeled off in all temperature environments, and the peeled off asphalt coating was embedded in the test piece by the abrasion tester, so it was impossible to measure. In Invention Example 1, the wear amount was smaller in the room temperature and 60°C environments than in the 0°C environment. In Invention Example 1, the wear amount was smaller in all of the 0°C environment, room temperature, and 60°C environments.

[0026] In the results of visual observation of the abrasion resistance test in a 0°C environment, in Comparative Example 1, the appearance was sound, as shown in FIG. 3(a). In Inventive Example 1, the exposure of the plating base was confirmed from the appearance, as shown in FIG. 3(b). In Inventive Example 2, the appearance was sound, as shown in FIG. 3(c). Therefore, by increasing the film thickness of the polyester resin-based paint, the abrasion resistance in a 0°C environment can be further improved. In the results of visual observation of the impact resistance test, in Comparative Example 1, partial peeling was confirmed at room temperature. In contrast, in Inventive Examples 1 and 2, both were sound at room temperature. In the results of visual observation of the impact resistance test, in Comparative Example 1, partial peeling was confirmed in a 60°C environment, as shown in FIG. 4(a). In contrast, in Inventive Examples 1 and 2, both were sound at a 60°C environment, as shown in FIG. 4(b) and FIG. 4(c). Therefore, the polyester resin-based paint can improve the abrasion resistance at room temperature and in a 60°C environment more than the asphalt paint.

[0027] In the impact resistance test in a 0°C environment, cracks and peeling were observed in the appearance of Comparative Example 1, as shown in FIG. 5(a). Inventive Example 1, there was no cracking or peeling in the appearance, as shown in FIG. 5(b). Inventive Example 2, there was no cracking or peeling in the appearance, as shown in FIG. 5(c). In the impact resistance test, visual observation showed that cracks and peeling were observed in Comparative Example 1 at room temperature, and no cracks or peeling were observed in a 60°C environment. Inventive Examples 1 and 2, there was no cracking or peeling in any of the 0°C, room temperature, and 60°C environments.

[0028] As shown in Table 3, Comparative Example 1 and Invention Examples 1 and 2 have good adhesion, scratch hardness, and rubbing properties.

[0029] Next, the abrasion resistance and impact resistance were evaluated for Example 3 and Comparative Example 1. The corrosion resistance, water resistance, and chemical resistance were further evaluated for Example 3 and Comparative Example 1. In evaluating the corrosion resistance and water resistance, two types of test specimens were prepared and tested: a fully painted specimen simulating a state in which the paint was in good condition, and a half-painted specimen simulating a state in which part of the paint had peeled off.

[0030] The abrasion resistance and the evaluation of the abrasion resistance were the same as described above, and therefore detailed explanations are omitted.

[0031] For corrosion resistance, a salt spray test was conducted in accordance with "JIS K 5600-7-1: Neutral salt spray resistance," and a combined cycle corrosion test was conducted in accordance with "JIS K 5600-7-9: Cyclic corrosion test method - salt spray / dry / wet." For corrosion resistance, a specimen was deemed to have passed if there was no cracking, blisters, or peeling observed visually.

[0032] Water resistance was evaluated by a submersion test according to "JIS K 5600-6-2: Liquid resistance (water immersion method)". If there was no cracking, swelling or peeling when visually observed, the product was deemed to have passed the test.

[0033] Chemical resistance was evaluated by a chemical resistance test according to "JIS K 5600-6-1: Liquid resistance (general method)" and if there was no cracking, swelling or peeling by visual observation, it was deemed to have passed. When evaluating chemical resistance, the specimen was immersed in a 10% sulfuric acid solution, a saturated sodium hydroxide solution, a 10% hydrochloric acid solution, a sodium hydroxide solution, kerosene, and ethanol.

[0034] The test outline and results are shown in Table 4. In Table 4, the test results and the overall evaluation based on the test results are indicated as "O" if they passed, and "X" if they failed.

[0035] [Table 4]

[0036] As shown in Tables 2 and 4, the coating thickness of Example 3 was 300 μm, and that of Comparative Example 1 was 1000 μm. Example 3 was evaluated as having abrasion resistance and impact resistance. In contrast, Comparative Example 1 was evaluated as not having abrasion resistance and impact resistance. Thus, Example 3 can have a thinner coating thickness than Comparative Example 1, and has impact resistance and abrasion resistance.

[0037] In detail, the abrasion amount in the abrasion resistance test was not measurable in Comparative Example 1 because the applied asphalt coating peeled off in all temperature environments and the peeled off asphalt coating was embedded in the test piece by the abrasion tester. Inventive Example 3 passed the test in all temperature environments.

[0038] As a result of visual observation in the abrasion resistance test, the appearance was sound in the 0°C environment in Comparative Example 1 and Invention Example 3. In Comparative Example 1, partial peeling was confirmed in the room temperature and 60°C environments. In contrast, both Invention Example 3 were sound. Therefore, the polyester resin-based paint can improve the abrasion resistance in the room temperature and 60°C environments more than the asphalt paint.

[0039] In the impact resistance test in a 0°C environment, Comparative Example 1 had cracks and peeling in appearance, as shown in Fig. 6(a). Invention Example 3 had no cracks or peeling in appearance, as shown in Fig. 6(b). Thus, Invention Example 3 has higher impact resistance in a 0°C environment than Comparative Example 1.

[0040] In the impact resistance test in a room temperature environment, Comparative Example 1 had cracks and peeling in appearance, as shown in Fig. 7(a). Inventive Example 3 had no cracks or peeling in appearance, as shown in Fig. 7(b). Thus, Inventive Example 3 has higher impact resistance in a room temperature environment than Comparative Example 1. In a 60°C environment, Comparative Example 1 and Inventive Example 3 had no cracks or peeling.

[0041] In a salt spray test on the fully painted surfaces, there were no cracks, blisters, or peeling in the appearance of Comparative Example 1 and Inventive Example 3. In a salt spray test on the half-painted surfaces, there were no cracks, blisters, or peeling in the appearance of Comparative Example 1, as shown in Figure 8(a). Similarly, there were no cracks or blisters in the appearance of Inventive Example 3, as shown in Figure 8(b).

[0042] In the combined cycle corrosion test with the full coating, Comparative Example 1 and Inventive Example 3 showed no cracks, blisters, or peeling in appearance. In the combined cycle corrosion test with the half coating, Comparative Example 1 showed cracks, blisters, and peeling in appearance, as shown in Figure 9(a). Inventive Example 3 showed no cracks, blisters, or peeling in appearance, as shown in Figure 9(b). It was therefore confirmed that Inventive Example 3 has higher corrosion resistance than Comparative Example 1.

[0043] In a submersion test on the fully painted surface, there were no cracks, blisters, or peeling in the appearance of Comparative Example 1 and Invention Example 3. In a submersion test on the partially painted surface, there were no cracks, blisters, or peeling in the appearance of Comparative Example 1, as shown in Figure 10(a). Similarly, there were no cracks or blisters in the appearance of Invention Example 3, as shown in Figure 10(b).

[0044] In a chemical resistance test in which the sample was immersed in kerosene, cracks, blisters, and peeling were observed in the exterior of Comparative Example 1, as shown in Fig. 11(a). In Invention Example 3, there were no cracks or blisters in the exterior, as shown in Fig. 11(b). Therefore, it was confirmed that Invention Example 3 has higher kerosene resistance than Comparative Example 1.

[0045] In a chemical resistance test in which the samples were immersed in a 10% aqueous sulfuric acid solution, a saturated aqueous sodium hydroxide solution, a 10% aqueous hydrochloric acid solution, an aqueous sodium hydroxide solution, and ethanol, Comparative Example 1 and Invention Example 3 showed no cracks, blisters, or peeling in appearance. [Explanation of symbols]

[0046] 1: Corrugated steel plate 2: Steel plate main body 3: Plating material 4: Synthetic resin paint 100: Waterway

Claims

1. A corrugated steel plate body portion; A plating material provided on the steel plate main body portion; and a synthetic resin paint applied to the plated material. A corrugated steel sheet characterized by:

2. The thickness of the synthetic resin coating is 10 μm or more and 500 μm or less. The corrugated steel sheet according to claim 1 .

3. The synthetic resin paint is composed of at least one of an epoxy resin paint and a polyester resin paint. The corrugated steel sheet according to claim 1 .

4. Used in waterways The corrugated steel sheet according to claim 1 .

Citation Information

Patent Citations

  • Asphalt-coated and corrugated steel plate for water way

    JP2009275353A